FEATURES OF THE CLINICAL COURSE OF PSORIASIS IN PATIENTS WITH OBESITY - Ya.O. Yemchenko; K.Ye. Ischeikin (Проблеми екології та медицини)
Psoriasis is the most common chronic, genetically determined autoimmune polyetiological inflammatory disease with impaired epidermal proliferation, provoked by exogenous and endogenous factors, and manifested by erythematous and scaly elements, papules and plaques. According to the results of clinical and epidemiological studies, psoriasis affects about 3-4% of the population of our planet, regardless of gender, age, and ethnic group, and the specific gravity of this pathology in the general structure of skin diseases reaches, from the data of different authors, from 1% to 40 %. However, despite the significant incidence of psoriasis and a large amount of research on this problem, there is still no single view of the pathogenesis of this dermatosis. For an objective understanding of the pathogenesis of psoriasis, it is necessary to take into account the insufficiently studied comorbidity of this pathology. Therefore, in the studies of the pathogenesis of psoriasis in recent years, more attention is paid to the impairment of metabolic processes. Recently, an indisputable link between psoriasis and obesity has been proven. Obesity has been found to increase the risk of many diseases, including psoriasis. The literature has broadly highlighted the question of the pathogenetic mechanisms of inflammatory processes in psoriasis and obesity that form a vicious circle at the level of the immune system, which must be broken for the successful treatment of these diseases. In this research, we studied the clinical presentation of the disease, measured anthropometric parameters, determined the grade of obesity by BMI, analyzed the history of life and disease, and conducted clinical and biochemical blood tests. The results of the study revealed that alimentary obesity in patients with psoriasis leads to metabolic disorders, complicating the course of dermatosis, which leads to a worsening of the DLQI of patients, the inefficiency of standard methods of therapy and frequent exacerbations of psoriatic disease. Therefore, the prospect for further research is a more in-depth study of the comorbidity of psoriatic disease, which will identify new targets for the treatment of this dermatosis to prevent complications and more effective treatment of this pathology.